(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article focuses on the significance of dialect-specific words and phrases in a piece of literature. This text explores the significance of dialectisms in M. Sholokhov’s novel "Quiet Don".